2017
DOI: 10.1016/j.amjsurg.2017.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in common laparoscopic abdominal surgical operations

Abstract: Laparoscopic colorectal operations for benign disease is at higher risk for development of VTE compared to other laparoscopic abdominal operations. Further studies should be performed to elucidate the underlying mechanisms for our finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The rates of symptomatic VTE (0.3%) and post‐operative bleeding (2.4%) in our cohort are comparable to international studies 14–23 . Importantly, our findings reflect those seen in patients who have undergone hip arthroplasty and spinal surgery, 11,12 that when compared with early chemoprophylaxis, its post‐operative use is associated with a lower risk of bleeding without compromising protection against thromboembolism.…”
Section: Discussionsupporting
confidence: 83%
“…The rates of symptomatic VTE (0.3%) and post‐operative bleeding (2.4%) in our cohort are comparable to international studies 14–23 . Importantly, our findings reflect those seen in patients who have undergone hip arthroplasty and spinal surgery, 11,12 that when compared with early chemoprophylaxis, its post‐operative use is associated with a lower risk of bleeding without compromising protection against thromboembolism.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings have practical implications for the prevention of VTE after bariatric surgery. By using a simple weight‐adjusted, once‐daily tinzaparin‐based VTE prophylaxis protocol, we demonstrated postoperative VTE rates that appear similar to or lower than those in cohort studies in which weight‐based dosing was not used . The feasibility and efficacy of pharmacologic prophylaxis extended out of hospital have also been demonstrated in other high‐risk patient groups, including medical inpatients and colorectal cancer surgery .…”
Section: Discussionmentioning
confidence: 60%
“…8 It was also reported that increased IAP attributed to pneumoperitoneum 1 is associated with thromboembolic events during the postoperative period. 9 During LC, patients are in head-up position, and standard pressure pneumoperitoneum is maintained at 12-14 mmHg by CO 2 insufflation. This high-pressure pneumoperitoneum and head-up position act as risk factors for venous stasis in the lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…8 It was also reported that increased IAP attributed to pneumoperitoneum is associated with thromboembolic events during the post-operative period. 9…”
Section: Introductionmentioning
confidence: 99%